(untitled) (Journal of Advanced Research in Journalism & Mass Communication, 2018)
Television plays a vital role in the form of communication for children’s. From the beginning Back from the days of media reports on how media has successfully presented and caricatured the children. In this paper we have primarily focussed on the television soaps and serials of Tamil and attempt to analyse how exactly do they present children and how successful are they in their presentation of reality? Or is this reality an imaginative one? Therein begins my analysis. The nation which claims to be in the process of “globalisation” or “modernisation” still portrays the children in meaningless masses of the group. When Children of India are progressing to be a doctor or an engineer, all these contemporary “slice-of-life” soaps are still entangled in household plots and schemes. Even with some attempts to actually portray reality, Tamil serials have not evolved beyond the monochromatic dimensions and a tricky vamp. The Study has incorporated the Content Analysis method. And we did content analysis of one popular serial from the popular Tamil television channels. How to cite this article: Shankaran KRS, Ilamparithi V. A Study on Portrayal of Children in Tamil Television Serials. J Adv Res Jour Mass Comm 2018; 5(4): 30-33.